Intranasal delivery of quercetin-loaded mucoadhesive nanoemulsion for treatment of cerebral ischaemia. (19th May 2018) - Ahmad, Niyaz; Ahmad, Rizwan; Naqvi, Atta Abbas; Alam, Md Aftab; Ashafaq, Mohammad; Abdur Rub, Rehan; Ahmad, Farhan Jalees
Abstract: Background: Quercetin (QUR), as an antioxidant flavonoid, exhibits potential role in the amelioration of cerebral ischaemia; however, poor solubility as well as oral absorption results low serum and tissue levels for this drug. Purpose of the study: To enhance bioavailability, this study aims to prepare QUR nanoemulsions and administer via non-invasive nasal route in order to evaluate the drug targeting in brain. Methods: Quercetin mucoadhesive nanoemulsion (QMNE) was prepared (ionic gelation method) and optimized using various parameters, that is, particle size, entrapment efficiency, zeta potential and ex vivo permeation study. Results: The results observed for optimized QMNE were as follows: mean globule size (91.63 ± 4.36 nm), zeta potential (−17.26 ± 1.04 mV), drug content (99.84 ± 0.34%) and viscosity (121 ± 13 cp). To evaluate the extent of bioavailability for QMNE via post-intranasal (i.n.) administration, Ultra performance liquid chromatography-mass spectroscopy (UPLC-ESI-Q-TOF-MS/MS)-based bioanalytical method was developed and validated for pharmacokinetics, biodistribution, brain-targeting efficiency (9333.33 ± 39.39%) and brain drug-targeting potential (2181.83 ± 5.69%) which revealed enhanced QUR brain bioavailability as compared to intravenous administration (i.v.). Furthermore, improved neurobehavioral activity (locomotor and grip strength), histopathology and reduced infarction volume effects were observed in middle cerebral artery occlusion (MCAO)–induced cerebral ischemic rats model after i.n. administration of QMNE. Conclusion: This study supports a significant role for QMNE in terms of high brain-targeting potential and formulation efficiency due to ease of access and effective targeting in brain. Graphical Abstract: